Tuberous Sclerosis Complex (TSC) Making the Invisible Visible - Vasseghi, Mary (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2025)
Tuberous Sclerosis Complex (TSC) is an autosomal dominant, multisystem genetic disorder, caused by a pathogenic variant in the TSC1 or TSC2 gene. It is characterised by the growth of benign tumours in numerous organ systems, including the brain, skin, heart, lungs, kidney. The most significant manifestations are epilepsy, TSC Associated Neuropsychiatric Disorders (TAND) and renal and pulmonary complications. It is a progressive disease, which requires lifelong surveillance and management. Based on an estimated international birth prevalence of 1:6,000-1:10,000, there should be approximately 500-600 people with a diagnosis of TSC in The Republic of Ireland (ROI). International TSC consensus recommendations defining the best approach to managing TSC exist. Personalised multidisciplinary care, ideally in a TSC centre of expertise is recommended. People with a diagnosis of TSC in the Republic of Ireland do not have access to a specialist TSC clinic or formalised TSC care network and there is a paucity of information concerning their experience of living with the disease and the healthcare they are receiving. Considerable progress in the understanding of TSC has been made in recent years. This has led to the development of novel targeted therapeutics and new surveillance and management strategies, generating disease modifying effects. It is vital people with TSC obtain an early diagnosis and receive optimal personalised care for their condition throughout their entire lifespan. Research Questions, Aims and Objectives of the research project . The primary aim of the study was to build a body of data, to inform the development of an internationally recognised standard of care for individuals with a diagnosis of TSC in the Republic of Ireland. Research Question What are the gaps in, barriers to, and facilitators of access to standardised healthcare for individuals with a diagnosis of Tuberous Sclerosis Complex in the Republic of Ireland? Objectives and methods A mixed method design, comprising four studies was applied to collect a range of objective and subjective data. A clinical audit assessing compliance with TSC United Kingdom (UK) guidelines within twelve epilepsy services was performed. Thirty-four semi structured in-person interviews with individuals with a diagnosis of TSC, and their families/carers were completed. Twenty-four in-person semi structured interviews with healthcare professionals who provide care for TSC patients were carried out. A previously validated patient survey on the burden of illness (BOI) and quality of life (QOL) of individuals with TSC was conducted. Thematic analyses were employed for the qualitative data generated by the interviews and descriptive statistical analysis were performed on the quantitative data from the audit and patient survey. Findings Study 1 (Clinical Audit) . One hundred and thirty-five TSC patients attending twelve epilepsy centres were identified. Adults (n= 67) paediatric (n= 68). The care of eighty-three patients was audited, (n=63 18yrs.) and (n=20 < 18 yrs.). The number of patients attending epilepsy services was lower than expected . Based on the frequency of epilepsy in TSC (84%) and a prevalence of TSC 1:60001:10,000, an estimated 400 patients would be expected to attend epilepsy services. Many baseline tests were completed, however, no patient in either the adult or paediatric groups had had a Tuberous Sclerosis Associated Neuropsychiatric Disorder (TAND) assessment completed. Intra or interhospital referrals were required for many services. Care appeared fragmented and there was no evidence of formal disease surveillance plans in either the adult or paediatric services. Study 2 (Lived experience of people living with a diagnosis of TSC (PLW TSC) and their families). Thirty-four in-person interviews were conducted with people living with TSC (PLW TSC) and their families/carers. The complexity of TSC was reflected in the heterogeneity of experiences. Difficult to control epilepsy and/or Tuberous Sclerosis Neuropsychiatric Disorders (TAND) manifestations were identified as particularly problematic. Patients and families demonstrated resilience in how they overcame the multitude of challenges in their daily lives as well as difficulties in their experiences of and navigating the healthcare services. Poor disease awareness in the healthcare community, lack of care coordination, communication challenges, poor access and long waiting times to certain services, were reported. However, many participants commended the healthcare professionals providing their care. Study 3 (Healthcare professionals perspectives on TSC care ) Twenty-four in person interviews with healthcare professionals (HCPs) who provide care to PLW TSC were conducted. HCPs encountered challenges in providing unified care for TSC patients, stating the rarity and complexity of the disease posed them difficulties in clinical practice. They identified shortcomings in the structure and operations of the healthcare system as not conducive to providing care for such a rare and complex disease. They recognised TSC awareness and knowledge within the healthcare community as poor and called for changes such as electronic records and systems, patient registry, education programmes and care pathways to facilitate care provision. They appreciated working in multidisciplinary teams and recognised the essential role of nurses, especially Advanced Nurse Practitioners. There was consensus a centre/network of coordinated TSC expertise was required. Study 4 (Survey of Burden of Illness and quality of life). This survey collected data of forty-two people with a diagnosis of TSC in the ROI. Adults (N=19), Paediatric (N=23). A subsection of people with a diagnosis of epilepsy, Adults (N=10), Paediatric (N=14), provided additional information on the impact of epilepsy on their lives. Overall, across the study the burden of disease was high, and the quality of life was low for PLW TSC and their families. Data showed the negative impact of TSC on the social wellbeing and family life of all groups. Fragmented healthcare and inadequate social supports contributed to the distress of participants. Conclusion This is the first study in the Republic of Ireland (ROI) and internationally to report on the impact of TSC on people (adult and children) living with TSC (PLW TSC) and their families from a broad standpoint, as well as on the perspectives of healthcare professionals (HCPs) providing TSC healthcare in the ROI. In-person semi structured interviews, an audit of TSC care in epilepsy services and patient survey on burden of illness and quality of live were conducted. The research demonstrated the heterogeneity of TSC as a differentiating factor for PLW TSC and their families as well as the HCPs providing their care. The severity of TSC symptoms, particularly epilepsy and Tuberous Sclerosis Associated Neuropsychological Disorders (TAND) negatively impact PLW TSC and their families. HCPs identified structural and operational challenges within the healthcare system impacting their capacity to deliver unified care to their TSC patients. The healthcare of PLW TSC is fragmented with no evidence of formal disease surveillance or coordinated care except in one adult epilepsy service, and navigating the healthcare system is reported to be challenging. PLW TSC and HCPs alike, identify widespread lack of awareness about TSC amongst HCPs. There is consensus amongst HCPs and PLW TSC and their families, that a coordinated approach to the delivery of personalised care, adhering to TSC consensus international recommendations, preferably in a centre/network of excellence is required.
APPROVED
Keywords: Tuberous Sclerosis Complex; Tuberous Sclerosis; Rare Disease; TSC; TSC1; TSC2; Multiorgan; Epilepsy; Nephrology; LAM; Lived Experience; Mixed Methods; TAND; Integrated care; Coordinated Care